Ayurveda management of chronic non healing pressure ulcer at foot secondary to tethered cord syndrome - A case report - Ramesh Killedar; Rajashekhar Sanapeti; Pradeep Shindhe (Wolters Kluwer Medknow Publications, 2018)
Pressure ulcers are classic chronic ulcers that appear over the areas of pressure and trauma in the skin that has lost sensation. Tethered cord syndrome is a rare etiology of chronic pressure ulcer originating from the central nervous system. Surgical treatment adopted is release of the tethered cord which promotes healing of the foot ulcers. We report a case of chronic pressure ulcer at foot since 8 years which was secondary to tethered cord syndrome. The case was diagnosed as dustavrana (non healing ulcer) as per classics and treatment was planned with Ksharakarma, Vimlapana and Basti. Local and Systemic treatment of pressure ulcer took 3 months for complete healing but there were no significant changes in reduced sensation of foot and thigh. The ulcer was successfully managed with Ayurveda treatment.